2021
DOI: 10.1002/bmc.5101
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic–pharmacodynamic modeling analysis and anti‐inflammatory effect of Wangbi capsule in the treatment of adjuvant‐induced arthritis

Abstract: Clinically, Wangbi Capsule (WBC) is widely used in the treatment of Rheumatoid arthritis (RA) because of its remarkable therapeutic effect. To reveal the mechanism, a pharmacokinetic-pharmacodynamic (PK-PD) model was developed for the first time to assess the relationship between time-concentration (dose)-effect. Freund's Complete Adjuvant was used to induce the adjuvant-induced arthritis model. Multiindices were used to evaluate the therapeutic effect and an S-I max PK-PD model was established based on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Previous studies reported the potential anti‐RA effect of OS 25,26 . In addition, OS has an inhibitory impact on cell proliferation, migration, and invasion 27,28 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies reported the potential anti‐RA effect of OS 25,26 . In addition, OS has an inhibitory impact on cell proliferation, migration, and invasion 27,28 .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies reported the potential anti‐RA effect of OS. 25 , 26 In addition, OS has an inhibitory impact on cell proliferation, migration, and invasion. 27 , 28 In the present investigation, we found that OS not only inhibited RA‐FLS proliferation, migration, and invasion but also showed an additive effect with MTX.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin and kaempferol remarkably suppressed production of PGE2 in human rheumatoid arthritis fibroblast-like synoviocytes (RAFLS), and the mechanism might be related to the inhibition of COX1 and COX2 expression ( Lee and Kim, 2010 ; Sung et al, 2012 ; Yoon et al, 2013 ). PGE2 and COX2 were suppressed by quercetin, emodin and icariin in RA mice ( Zhu et al, 2013 ; Yang et al, 2018b ; Guazelli et al, 2018 ; Liu T et al, 2021 ). Apigenin, isoliquiritigenin and luteolin treatment had an inhibitory effect on the expression of COX2 in lipopolysaccharide (LPS) induced RAW 264.7 macrophage cells ( Kim et al, 2008 ; Lee and Kim, 2010 ).…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 98%
“…The expression of VEGF, VEGFR1 and VEGFR2 in synovial tissues of CIA mice and vascular cell adhesion molecule (VCAM) in human umbilical vein endothelial cells (HUVECs) were significantly inhibited by apigenin ( Li et al, 2019 ; Zhou et al, 2021 ). A recent study showed that luteolin suppressed the expression of VEGF and HIF-1α in CIA mice and HUVECs ( Liu T et al, 2021 ; Zhou et al, 2021 ). In vivo and in vitro studies showed that β -sitosterol significantly inhibited the expression and phosphorylation of VEGFR2 ( Qian et al, 2021 ).…”
Section: Antiangiogenic Activitiesmentioning
confidence: 99%
“…It has been reported that CN could inhibit the inflammatory responses of RAW264.7 cells, ameliorate imiquimod‐induced psoriasis, and suppress allergic inflammation [15–17]. Recently, it was found that MV might be one of the main effective substances of Wangbi capsules in the treatment of rheumatoid arthritis [18]. Due to their various pharmacological activities, PG and MV are used as quality control indicators of SD in the Chinese Pharmacopoeia.…”
Section: Introductionmentioning
confidence: 99%